2020
DOI: 10.1080/14767058.2020.1849105
|View full text |Cite
|
Sign up to set email alerts
|

Non-prescribed drug use and predictors among pregnant women in Ethiopia: systematic review and meta-analysis

Abstract: Background: The use of non-prescribed drugs are common to pregnant women. It may lead to undesirable effects, such as birth defects. Study results on the occurrence and predictor of non-prescribed drug use among pregnant women throughout Ethiopia are highly variable and inconsistent. Therefore, the objective of this systematic review and meta-analysis was to estimate the pooled prevalence of non-prescribed drug use and predictors among pregnant women in Ethiopia. Methods: We systematically searched studies fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 54 publications
(59 reference statements)
5
6
0
Order By: Relevance
“…In consonance with many previous studies [126] it is concerning that antimicrobials are among the top three groups of medicines used for self-medication in this study (Paper III). Furthermore, antimicrobials were irrationally used and gave rise to MRPs in the inpatient setting (Paper IV).…”
Section: Safety Concerns and Mrps Of Conventional Medicinessupporting
confidence: 88%
See 3 more Smart Citations
“…In consonance with many previous studies [126] it is concerning that antimicrobials are among the top three groups of medicines used for self-medication in this study (Paper III). Furthermore, antimicrobials were irrationally used and gave rise to MRPs in the inpatient setting (Paper IV).…”
Section: Safety Concerns and Mrps Of Conventional Medicinessupporting
confidence: 88%
“…On the other hand, the study findings showed that the majority of women admitted to the hospital (85.2%) used one or more prescription or non-prescription medicines (excluding vaccinations) prior to hospitalization. In line with previous studies from other geographical areas of Ethiopia [126], most of the pharmaceutical medicines used for self-medication were analgesics (Paper III) for the relief of pain or inflammation. This is corroborated by previous findings that Ethiopians employ self-medication for illnesses that are perceived as mild [34,42].…”
Section: Reasons For Use Of Medicinal Plants and Conventional Medicinessupporting
confidence: 85%
See 2 more Smart Citations
“…Stata, version 15.1 (StataCorp. ), was utilized to collect data and to perform relevant analyses in this meta-analysis (Gebrie et al, 2019;Adane et al, 2020). Each numerical value of the result was presented with a 95% confidence interval (95% CI).…”
Section: Data Synthesis and Statisticsmentioning
confidence: 99%